Makanan Pendamping ASI (MP-ASI) dengan Kejadian Stunting pada Anak Balita - Stephanie Lexy Louis; Ayu Nina Mirania; Evi Yuniarti (Jurnal Ilmiah Kesehatan (JIKA), 2022)
Stunting is a long-term abnormal condition experienced by children under five years with z-score values less than -2SD and less than -3SD. This study aims to determine the relationship between complementary feeding (MP-ASI) and the incidence of stunting in children under five years, exactly within 12-59 months. This type of research was using an analytic survey with a cross-sectional design of 30 samples selected by random sampling from September 2021 to November 2021. Meanwhile, data collection was carried out by measuring height, interviews, and filling out questionnaires. Whereas, for data analysis was using a chi-square test (p-value <0,05). The results showed that there was a relationship between the variable age of breastfeeding, indicated by a value of p=0,014, while the frequency variable for MP-ASI showed p=0,68 and for the type of complementary feeding variable, the results were p=0,22. Overall, this study concludes that there is a relationship between the age of complementary feeding and the incidence of stunting in children under five years of age 12-59 months, while the variable frequency of giving complementary feeding and the type of complementary feeding has no relationship with the incidence of stunting in children aged 12-59 months.